Statistical approach to synthesise biogenic silica nanoparticles from rice husk and conjugated with Justicia adhatoda extract as green, slow‐release biocide - Peerzada Gh Jeelani; C Ramalingam (IET Nanobiotechnology)
Abstract Biogenic silica synthesised from rice husk was used as a controlled release system of an eco‐friendly biocide consisting of a Justicia adhatoda extract. Fourier‐transform infrared spectroscopy (FTIR) indicated the presence of ester bonds between the silica support and the conjugated Justicia adhatoda extract. Surface area analysis and microscopy confirmed a high level of Justicia adhatoda extract loading in the silica support. The phytochemical investigation of Justicia adhatoda was done by Gas chromatography–mass spectrometry (GC‐MS) spectroscopy. Moreover, compared with the naked biogenic silica nanoparticles, a better thermal stability was determined for the conjugated system of the extracted compounds. Trial of kinetic release of silica: Justicia adhatoda ∼29% of loaded Justicia adhatoda was released within 1 h and then the rate of release became slow. Net release of Justicia adhatoda was observed up to 50% within 7 h. The Justicia adhatoda compounds released from silica also showed the improved mortality rate against stored product pest rice weevil (Sitophilus oryzae).